The Impact of macroeconomic policies on poverty and income distribution : (The World Bank, 2008)
This book reviews techniques and tools that can be used to evaluate the poverty and distributional impact of economic policy choices. It describes the most robust techniques and tools now available-from the simplest to the most complex-and identifies best practices. The tools reviewed here help quantify the trade-offs and consequences of economic policies that affect countries through various channels. Each chapter addresses a specific evaluation technique and its applications, and household survey data are used for descriptions of economic welfare distribution. The focus is on the micro level in the first part of the book, and links between macro modeling and the microeconomic distribution of economic welfare are the focus of in the last five chapters.